Relationship between thoracic kyphosis and neural axis abnormalities in patients with adolescent idiopathic scoliosis. (February 2018) - Swarup, I.; Derman, P.; Sheha, E.; Nguyen, J.; Blanco, J.; Widmann, R.
Purpose: Previous studies have suggested an association between increased thoracic kyphosis and neural axis abnormalities in patients with adolescent idiopathic scoliosis (AIS). However, the basis for this finding is unclear, and this association has been mainly noted in retrospective studies on a non-consecutive series of patients. The purpose of this study was to assess the relationship between thoracic kyphosis and neural axis abnormalities in patients with AIS. Methods: We studied a consecutive series of AIS patients treated with spinal fusion. Thoracic kyphosis (T2 to T12) was measured from preoperative lateral radiographs. All patients underwent a spine magnetic resonance imaging (MRI) prior to surgery, and MRI reports were reviewed to determine the presence of neural axis abnormalities. Statistical analyses included descriptive statistics and chi-squared analysis. Results: This study included 210 patients with AIS. There were no significant differences in age or gender between patients with thoracic hypokyphosis (kyphosis < 20°), normal thoracic kyphosis (kyphosis 20° to 40°) and thoracic hyperkyphosis (kyphosis > 40°) (p > 0.05). Neural axis abnormalities were present in 17.9% of patients with thoracic hypokyphosis, 9.8% of patients with normal thoracic kyphosis and 13.6% of patients with thoracic hyperkyphosis (p = 0.60). There were no significant differences in rates of Chiari malformation, syrinx, intra-spinal masses and other central nervous system abnormalities between groups (p > 0.05). Conclusions: Thoracic kyphosis was not associated with neural axis abnormalities in our consecutive series of patients with AIS. Increased thoracic kyphosis may not be a reliable indicator for the presence of neural axis abnormalities in patients with AIS. Level of Evidence: IV